The memory effect for particle scattering in even spacetime dimensions. (29th June 2017) - Garfinkle, David; Hollands, Stefan; Ishibashi, Akihiro; Tolish, Alexander; Wald, Robert M
Abstract: We explicitly calculate the gravitational wave memory effect for classical point particle sources in linearized gravity off an even dimensional Minkowski background. We show that there is no memory effect in d   >  4 dimensions, in agreement with the general analysis of Hollands et al (2016 arXiv:1612.03290).